PREDICTING INTENDED UNETHICAL BEHAVIOUR AMONG COLLEGE OF ECONOMICS AND BUSINESS STUDENTS: AN EMPIRICAL STUDY AT UNIVERSITAS GADJAH MADA - Sari Winahjoe; Sudiyanti Sudiyanti (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
This study attempted to examine the intention to act in an unethical manner among the economics and business students in Universitas Gadjah Mada by applying the Theory of Planned Behaviour. Attitude, subjective norms, perceived personal outcome, perceived social acceptance, and perceived behavioural control were included in predicting this intention. A total of 208 students participated in the main investigation. Using ordinal regression, 3 hypothetical unethical situations were proposed to measure the students’ intended behaviour: (1) having the class attendance list signed by a classmate; (2) cheating in an examination or quiz; and (3) knowingly plagiarising someone else’s work. The results confirmed that attitude was the strongest predictor of a student’s intention to act in an unethical manner. The study findings also supported subjective norms as the second strongest predictor, which was followed by perceived personal outcome and perceived social acceptance as determinants of such behavioural intention. Meanwhile, the findings demonstrated that perceived behavioural control was the weakest predictor of intention. Analysis for each situation, implications for practitioners, specifically university teachers and education policy makers, and further research recommendations are also discussed.